Application of deep learning in MRI classification of Schizophrenia - Joyee, Ramisa Fariha; Rodoshi, Lamia Hasan; Nadia, Yasmin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.